1978
DOI: 10.1084/jem.147.3.854
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of autoimmunity and retrovirus expression in crosses of New Zealand black mice I. Xenotropic virus.

Abstract: Type C RNA viruses (retroviruses) have been implicated in the autoimmune disease of New Zealand Black (NZB) 1 mice (1, 2). However, the evidence for this is only circumstantial because the retroviruses isolated from NZB mice are xenotropic in host range; this prohibits a direct test of their pathogenicity in mice by, for example, inoculation of filtrates (3, 4). Nevertheless, the relationship between autoimmunization and xenotropic viruses c&n be ascertained by genetic tests because the genes of these agents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Presently there is no evidence that the lymphocyte membrane antigen(s) detected with the extensively absorbed anti-SLE antisera described here have any relationship to virus or cell surface determinants related to any viral genome (37)(38)(39)(40). Considerably more work will be necessary before such a possibility can be resolved.…”
Section: Resultsmentioning
confidence: 94%
“…Presently there is no evidence that the lymphocyte membrane antigen(s) detected with the extensively absorbed anti-SLE antisera described here have any relationship to virus or cell surface determinants related to any viral genome (37)(38)(39)(40). Considerably more work will be necessary before such a possibility can be resolved.…”
Section: Resultsmentioning
confidence: 94%
“…63 In contrast to NZW, which can develop mild nephritis late in life, the SWR1 mouse is completely healthy and has a normal life span. Clinically, the SNF1 mouse is similar to BWF1 mice, with most females dead by 10-12 months and with a 50% mortality rate at 6 months of age with an immune glomerulonephritis that is mediated primarily by IgG2b antibodies to DNA.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Investigators have shown that the NZB xenotropic virus production is inherited as a dominant trait and is independent of the development of other autoimmune traits (Datta and Schwartz, 1976;Datta et al, 1978). Since virus production seems to be a dominant trait, the (NZB X DBA) F| mice should have high titers of virus, yet they did not have chromosomal abnormalities.…”
Section: Lack Oj Association Of Hyperdiploidy With Other Traitsmentioning
confidence: 99%